The Source Base Study of the History of Childrenʼs Movement in Ukraine - Nataliya Koliada (Pedagogical Discourse, 2013)
The article analyzes the source-base history of domestic childrenʼs movement. Summarizing the different scientific approaches, the author singles out the main sources of problems in the history of childrenʼs movement: real sources; filmphotophonodocuments, visual materials, written sources. Particular attention is devoted to the analysis of written sources (documents of parties, youth and childrenʼs organizations, published an appeal letters about the Young Pioneers party, government and public figures, statistical sources; materials periodicals, documents of educational, scientific and educational institutions and authorities of public education, memoirs, materials of the international childrenʼs movement).